Early expressive vocabulary skills: A multi-method approach to measurement. Issue 2 (April 2014) - Gatt, Daniela; Grech, Helen; Dodd, Barbara
Investigations of early vocabulary production often employ a single method to measure children's word use. This study examined expressive vocabulary development in children aged 1;0–2;6 years through a combination of picture naming, caregiver report and language sampling. The participants were predominantly exposed to Maltese at home, with gathered evidence providing novel documentation of early vocabulary development in this specific language-learning context. Expressive vocabulary reported by caregivers was compared to word use elicited through picture naming and sampled naturalistically during play. Analyses revealed commonalities between pairs of measures that pointed towards their validity. Resulting differences underscored the influences that data collection methods exerted on the measures they generated. Taken together, these findings highlight the relevance of multiple methods for ensuring validity and objectivity in the investigation of expressive vocabulary development.